Intra-group Services: Suatu Perspektif Fiskus - Ayrton Ramzy Soarer Zaki; Ferry Irawan (Politeknik Keuangan Negara STAN, 2022)
The purpose of the audit conducted by the Directorate General of Taxes is to test compliance or other purposes. This study aims to determine the auditors’ perception of service transactions carried out by related parties, the challenges experienced when examining transfer pricing on intra-group service transactions and the mechanism used in conducting transfer pricing adjustments to intra-group service transactions. The results of this qualitative study indicate that tax examiners who work in the Java region have a better perception when viewed from the area where they work. The results also show that auditors experience difficulties when carrying out audit procedures such as knowledge related to technical intra-group services, the situation of taxpayers being less cooperative, applicable regulations, data access, competence and personal examiners, as well as legal remedies from taxpayers. In addition, the results of the study also show that in general, the mechanism used by auditors to find corrections is through audit procedures that refer to the Circular Letter of the Director General of Taxes Number SE-50/PJ/2013 and Regulation of the Director General of Taxes Number PER-22/PJ/2013.